2021
DOI: 10.4067/s0717-92002021000300365
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the complete chloroplast genome of Prosopis tamarugo (Prosopis, Leguminosae), an endangered endemic tree species from the Atacama Desert

Abstract: Prosopis tamarugo (Prosopis, Sect. Strombocarpa) is an important endangered tree species from the Atacama Desert (Chile). However, this species requires urgent conservation measures, for which it is necessary to evaluate their genetic diversity. Here, we present the characterization of the complete chloroplast genome of P. tamarugo; the first complete chloroplast of a species from the Strombocarpa section, obtained by next generation sequencing (NGS) methods. The complete chloroplast contains 161,575 bp and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…However, the Strombocarpa species presented slightly more GC content (36.0%-36.2%) compared to the Neltuma species (35.9%). These GC values fall within the limit of variation registered in others studies 25,57 . Furthermore, a study about several orchid species, showed that the species with a smallest chloroplast size (Pholidota cantonensis, 158,786 bp), had a highest GC content (37.47%) 59 , similar to our observations.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…However, the Strombocarpa species presented slightly more GC content (36.0%-36.2%) compared to the Neltuma species (35.9%). These GC values fall within the limit of variation registered in others studies 25,57 . Furthermore, a study about several orchid species, showed that the species with a smallest chloroplast size (Pholidota cantonensis, 158,786 bp), had a highest GC content (37.47%) 59 , similar to our observations.…”
Section: Discussionsupporting
confidence: 86%
“…The chloroplast of N. alba and N. chilensis showed similar values for genome size and the number of genes compared to Neltuma juli ora and Neltuma glandulosa described by Asaf 57 , ~ 163.000 bp for both, while the number of genes varied between 131 and 128. The number of genes was similar between the Neltuma and Strombocarpa genera, although S. tamarugo lost the gene psbL (remaining with 127 genes only) 25 . The absence of the psbL gene has been observed in some other eudicots, magnoliids, and monocots as well 58 .…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The number of genes was similar between the Neltuma and Strombocarpa genera. Although S. tamarugo was thought to have lost the gene psbL (remaining with 127 genes only) 24 , we performed a new sequence annotation and finally found the reading frame of the gene. The genome sizes of S. strombulifera (160,569 bp) and S. tamarugo (161,575 bp) were smaller compared to the Neltuma species (~ 163.000 bp) 24 .…”
Section: Discussionmentioning
confidence: 99%